Anti-inflammatory Streptococcus thermophilus CNRZ160 limits sarcopenia induced by low-grade inflammation in older adult rats - Savary-Auzeloux, Isabelle; Jarzaguet, Marianne; Migné, Carole; Kemeny, Jean-Louis; Novais-Gameiro, Lorraine; de Azevedo, Marcela; Mathé, Véronique; Mariotti, François; Langella, Philippe; Chatel, Jean-Marc; Dardevet, Dominique (Frontiers in Nutrition, 2022)
Aging is characterized, at the systemic level, by the development of low-grade inflammation, which has been identified as determining sarcopenia by blunting postprandial muscle anabolism. The causes of this “inflammageing” is still not clearly defined. An increased intestinal permeability, a microbiota dysbiosis and subsequent generation of intestinal then generalized inflammation have been hypothesized. The objective of this study was to test in vivo during aging if 1) a chronic low-grade intestinal inflammation can lead to anabolic resistance and muscle loss and 2) if a bacterial strain presenting anti-inflammatory properties could prevent these adverse effects. Young adult (6 m) and elderly rats (18m) received Dextran Sodium Sulfate (DSS) for 28 days to generate low-grade intestinal inflammation, and received (PB1 or PB2 groups) or not (DSS group) one of the two S. Thermophilus strains (5x109 CFU / day) previously shown to present an anti-inflammatory potential in vitro. They were compared to pair fed control (PF). Muscle and colon weights and protein synthesis were measured at slaughter. Muscle proteolysis, gut permeability and inflammatory markers were assessed only in old animals. In both adult and old rats, DSS reduced absolute protein synthesis (ASR) in gastrocnemius muscle (-12.4% (PB1) and -9.5% (PB2) vs PF, P<0.05) and increased ASR in colon (+86% and +30.5% respectively vs PF, P<0.05). PB1 (CNRZ160 strain) but not PB2 presented a higher muscle ASR as compared to DSS in adults (+18%, P<0.05), a trend also observed for PB1 in old animals (+12%, P=0.10). This was associated with a blunted increase in colon ASR. In old rats, PB1 significantly decreased expression of markers of autophagy and ubiquitin-proteasome pathways vs DSS groups, improved gut permeability (Occludin, Zonula Occludens 1 and Claudin 1 expression, P<0.05) and alleviated systemic inflammation (A2M: -48% vs DSS, P<0.05). The loss of muscle anabolism associated with low-grade intestinal inflammation was prevented by supplementation with anti-inflammatory CNRZ160 strain. The moderated gut inflammation by CNRZ160 may result in curtailed amino acids (AA) utilization by the gut, and subsequent restored AA systemic availability to support muscle protein accretion. CNRZ160 could be considered as an efficient probiotic to limit sarcopenia during aging.